C. elegans nuclear receptor NHR‐6 functionally interacts with the jun‐1 transcription factor during spermatheca development. Issue 1 (18th November 2013) - Gissendanner, Chris R.; Cardin, Derrick; DuBose, Chris J.; El, Moustafa; Harmson, Jeremy S.; Praslicka, Brandon; Rowan, Brian G.
Summary The NR4A nuclear receptor NHR‐6 is an essential regulator of spermatheca organogenesis in C. elegans. In this study, we perform a focused, RNAi‐based screen to identify modifiers of partial nhr‐6 loss of function. Ninety‐eight genes that encode signaling proteins expressed in the spermatheca were screened for enhancement of the nhr‐6 RNAi phenotype. We identify the C. elegans gene jun‐1, which encodes the homolog of the Jun transcription factor, as a strong enhancer of nhr‐6 partial loss of function. We show that nhr‐6 and jun‐1 function together to regulate development of the spermatheca and are necessary for generating an organ with the normal number of cells. jun‐1 is expressed in all cells of the developing spermatheca. We also provide evidence that NHR‐6 and JUN‐1 can physically interact in a yeast two‐hybrid assay. Our results provide in vivo evidence that NR4A nuclear receptor and Jun transcription factor interactions are essential in regulating developmental processes in metazoans. genesis 52:29–38, 2014. © 2013 Wiley Periodicals, Inc.